Innovation Cooperation and Innovation Activity of Slovenian Enterprises - Andreja Jaklič; Jože P. Damijan; Matija Rojec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
Innovation cooperation has been recognised as an important detfirminant of enterprises?innovation activity, productivity, and growth, and has recently become the subject of intensive research. We explore the importance of innovation cooperation for the innovation activity of Slovenian enterprises, what kind of innovation cooperation is the most 'productive?for innovation activities, and whether the location and foreign ownership of innovation cooperation matters. Probit estimations confirmed external innovation cooperation as one of the most important incentives for innovation activity, after R&D spending. However, a significant influence was only confirmed for domestic and not for international innovation cooperation in general. The efficiency varies also by type of partners; while inter-firm innovation cooperation significantly increases the probability of innovation, this was not found regarding cooperation with universities and R&D institutes. The impact of innovation cooperation differs by distance; the contribution of EU partners to innovation activity was the highest (higher then that of domestic partners), while partners from other locations may even decrease the probability of innovation.
Keywords: D2; L2; O3; 330; innovation cooperation; innovation activity; foreign ownership; innovation partner; R&D; Slovenia; Innovation; Forschungskooperation; Direktinvestition; Innovationsdiffusion; Slowenien